MASALAH PERDAMAIAN DIHADAPAN MAJELIS HAKIM PERKARA PERDATA YANG TAK DAPAT DIMINTAKAN BANDING DAN AKIBAT HUKUMNYA - Oktario Sirait (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT That the powers of peace exercised before the courts have the same powers as the judges' ruling, so they are binding on both sides. The content of the peace set forth in the peace deed in the face of a judge is a punishment from a judge to comply with the agreed peace agreement. Another case when peace is held outside the session. This kind of peace is often successful, but this peace of law is not the same as peace in the congregation. For peace made by the parties is purely a matter of consent, the deed made to strengthen it is merely a deed under the hand. If either party denies it, a lawsuit may be filed and there is no possibility of the agreement being revoked. The legal consequence of a peace ruling is binding on the parties to the dispute. While the legal consequences of a peace ruling outside the congregation, if one of the parties denies the contents of the agreement, the aggrieved party may file a lawsuit again, so that it can not apply for such execution as the result of the law of the peace ruling in the hearing. Besides the legal consequences of the other peace ruling is that in the same case it can not be brought back a second time, because it has been completed thoroughly. As with the legal consequences of peace decisions being held outside the congrega- tion, a reconciliatory dispute outside the congregation can be said to be completed only temporally and does not guarantee that it will not be disputed anymore by the parties. Peace can not be appealed ie a verdict of peace that already has the force of law that remains meaningless since the beginning of the verdict of peace is not allowed to file an appeal request. Because at the time the verdict of peace is realized, it has been attached to the decision of the value of the power of the law as a verdict that has got the legal force remains. In addition to a permanent legal force, as well as to peace by parties of a similar nature, to such a peace can not be appealed or appealed.